Investigating Pre-Service English Teachers’ Experience in Implementing Tpack During Teaching Practice on Independent Curriculum - Nur Inayati efendi; Lestari, Iin Widya; Zumrudiana, Ainu; Zainuddin, Moh (Eduvelop: Journal of English Education and Development, 2024)
This study intends to ascertain (1) How do pre-service English teachers conceptualize TPACK and its components, (2) What challenges do pre-service English teachers encounter in implementing TPACK during teaching practice on independent curriculum, (3) What strategies do pre-service English teachers employ to address these challenges. The research participants were students of English Education study programs from different universities who have practiced teaching English in the independent curriculum. The data for this study were collected through questionnaires and interviews. The result of this study revealed, (1) many ways to conceptualize TPACK in learning such as utilizing technology such as PowerPoint, Canva, Google Form, Quizizz, and others. And also conceptualize pedagogy knowledge to approach students such as checking student understanding through questions at the end of learning and evaluating the concept of learning content based on how well students understand and are interested in the material, (2) These challenges come from internal and external factor such as lack of time to approach students, less responsive students, participants must always innovate to create interesting learning concepts that require process and consistency, (3) respondents have alternatives to face challenges in implementing TPACK, such as making a second plan if there are problems related to technology, asking questions and making approaches outside of class hours and respondents tried to increase their knowledge about TPACK by frequently from the internet.